Degradación por corta de aguajes en la diversidad, composición florística y los rasgos funcionales de la regeneración natural, Loreto, 2021 - Siles Diaz, Ana Lucero (2022)
The aguajales represent one of the ecosystems with the highest environmental and socioeconomic value in the Loreto region, where the predominant species is Mauritia flexuosa L.f. "aguaje". The growing demand for aguaje fruits in Amazonian cities has been generating an impact on the aguajales because of the destructive methods to harvest the fruit. The objective of the research was to determine the impact of the cutting of female palms in the floristic composition, diversity and functional traits of natural regeneration in aguajales. Five permanent plots of 0.5 ha were evaluated in aguajales in different stages of degradation, four plots in the Ucayali basin and one plot in the Yanayacu Pucate basin. The results show that the floristic composition, diversity and functional traits are changing along a gradient of degradation. In the floristic composition, the abundance of natural regeneration of aguaje decreased significantly as the level of degradation in aguajales increased (p. valor: 0.009, ??2: 92%). While the diversity of woody species and other palms increased as the level of degradation by cutting of female aguaje increases (Alfa de Fisher. valor: 0.009, ??2: 92% y Shannon: p. valor: 0.006, ??2: 94%). The composition of species in less degraded aguajales was composed of woody species and other palm trees demanding sunlight, but, as degradation increased, they were replaced by shade tolerant species (p. valor: 0.04, ??2: 79%). The functional traits showed that the wood density is susceptible to the changes generated by the degradation (p. valor: 0.1029, R^2: 64%), while the specific leaf area was not susceptible to degradation (p. valor: 0.7813, ??2: 2%).